Combined search for the standard model Higgs boson decaying to bb̄ using the D0 run II data set - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Askew, A.; Atkins, S.; Augsten, K.; et al. (American Physical Society (APS), 2012)
We present the results of the combination of searches for the standard model Higgs boson produced in association with a W or Z boson and decaying into bb̄ using the data sample collected with the D0 detector in pp̄ collisions at √s=1.96TeV at the Fermilab Tevatron Collider. We derive 95% C.L. upper limits on the Higgs boson cross section relative to the standard model prediction in the mass range 100GeV≤M H≤150GeV, and we exclude Higgs bosons with masses smaller than 102 GeV at the 95% C.L. In the mass range 120GeV≤M H≤145GeV, the data exhibit an excess above the background prediction with a global significance of 1.5 standard deviations, consistent with the expectation in the presence of a standard model Higgs boson. © 2012 American Physical Society.
Keywords: Background prediction; Cross section; Data sample; Data sets; Fermilab Tevatron collider; Higgs boson; Standard deviation; Standard-model Higgs bosons; The standard model; Upper limits; Z Bosons; Tellurium compounds; Bosons